Ionospheric GPS-TEC responses from equatorial region to the EIA crest in the South American sector under intense space weather conditions - de Abreu, Alessandro José (2022)
We present and discuss the ionospheric F-region observations from equator to the equatorial ionization anomaly (EIA) regions over the South American sector during an intense space weather event occurred between 27 and May 29, 2017. During this geomagnetic storm, the symmetric-H (SYM-H) reached a minimum of −142 nT at ∼0700 UT on May 28, 2017. For this investigation, we analyze the vertical total electron content (VTEC) observations from a chain of nearly 120 Global Positioning System (GPS) stations. Magnetometer measurements obtained at two stations in the low latitude regions are also presented. The observations do not indicate prompt penetration electric field (PPEF) effects in the VTEC variations. Magnetometer's observations over Cuiabá (CBA) and Cachoeira Paulista (CXP) in central west and south parts of Brazil, respectively, have shown a strong cross-correlation with SYM-H in the period between 3 and 48 h. The results also show positive ionospheric storm phase during the recovery phase on May 28, 2017. Positive effect during the recovery phase of the geomagnetic storm is possibly associated with effects of disturbances winds. During the recovery phase, a strong intensification of the EIA took place, possibly related to an additional ionization effect. The VTEC values show differences between the west and east sectors. This indicates that the EIA crest is stronger in the east sector than in the west sector, possibly due to the combination of disturbance wind effects and geomagnetic field geometry where in the east sector the field lines are more inclined.